A microbiological hazard of rural living: Clostridium septicum brain abscess in a child with E coli 0157 associated haemolytic uraemic syndrome. (26th June 2012) - Williams, Eleri J; Mitchell, Patrick; Mitra, Dipayan; Clark, Julia E
Abstract : Clostridium septicum infection in humans is rare and this is the second case report of focal C septicum brain abscesses associated with Escherichia coli 0157 haemolytic uraemic syndrome (HUS). The case presented in a child who lived on a rural farm. The abscesses initially progressed despite 7 months of appropriate antibiotic therapy and repeated image-guided aspiration. After definitive resection and prolonged antibiotic therapy, there was no recurrence. This case reminds us of this rare but important neurological complication of HUS and supports consideration of early definitive neurosurgical intervention in similar unusual cases.